Penerapan Metode Eksplorasi Lingkungan Sekitar dalam Peningkatan Pengetahuan Sains - Miswan Ramdani; Ardi Muhamad Arsyad (Institut Madani Nusantara, 2021)
The development of science and technology needs to be introduced to children from an early age, it is hoped that later as a community and the younger generation they can carry out and develop their potential and be responsive to actual problems related to the environment and technology. The purpose of this study was to determine the increase in children's science knowledge in the application of environmental exploration methods in increasing children's science knowledge. In this study, the authors use research methods that are quantitative and qualitative. Quantitatively, the collected data were analyzed descriptively by percentage. The approach used in this study is a Classroom Action Research (CAR) approach, with data collection techniques using observation, interviews, and documentation. The location of the research was carried out at Ananda Ceria Nagrak Kindergarten, Sukabumi Regency. The results of this study indicate that there is an increase in the science knowledge of Ananda Ceria Nagrak Kindergarten students through learning with the exploration method of the surrounding environment, which has been proven by observations on the activeness of students in expressing their scientific knowledge in cycle I and cycle II and cycle III. The teacher's ability to teach with the method of exploring the surrounding environment in cycle I, cycle II and cycle III gets a good category of application to students.